Choline Metabolism and Risk of Atrial Fibrillation and Heart Failure in the PREDIMED Study. (30th November 2020) - Papandreou, Christopher; Bulló, Mònica; Hernández-Alonso, Pablo; Ruiz-Canela, Miguel; Li, Jun; Guasch-Ferré, Marta; Toledo, Estefanía; Clish, Clary; Corella, Dolores; Estruch, Ramon; Ros, Emilio; Fitó, Montserrat; et al.
Abstract: Background: Few studies have examined the associations of trimethylamine-N-oxide (TMAO) and its precursors (choline, betaine, dimethylglycine, and L-carnitine) with the risk of atrial fibrillation (AF) and heart failure (HF). This study sought to investigate these associations. Methods: Prospective associations of these metabolites with incident AF and HF were examined among participants at high cardiovascular risk in the PREDIMED study (PREvención con DIeta MEDiterránea) after follow-up for about 10 years. Two nested case-control studies were conducted, including 509 AF incident cases matched to 618 controls and 326 HF incident cases matched to 426 controls. Plasma levels of TMAO and its precursors were semi-quantitatively profiled with liquid chromatography tandem mass spectrometry. Odds ratios were estimated with multivariable conditional logistic regression models. Results: After adjustment for classical risk factors and accounting for multiple testing, participants in the highest quartile vs. the lowest quartile of baseline choline and betaine levels had a higher risk of AF [OR (95% CI): 1.85 (1.30–2.63) and 1.57 (1.09–2.24), respectively]. The corresponding OR for AF for extreme quartiles of dimethylglycine was 1.39 (0.99–1.96). One SD increase in log-transformed dimethylglycine was positively associated with AF risk (OR, 1.17; 1.03–1.33). The corresponding ORs for HF for extreme quartiles of choline, betaine, and dimethylglycine were 2.51 (1.57–4.03), 1.65 (1.00–2.71) and 1.65 (1.04–2.61), respectively. TMAO and L-carnitine levels were not associated with AF or HF. Conclusions: Our findings support the role of the choline metabolic pathway in the pathogenesis of AF and HF.